“Sempre haverá pobres na terra”: os desafios da pobreza na América Latina dentro do novo paradigma de missão cristã segundo o Pacto de Lausanne e a Gaudium et Spes - Arruda, Glair Alonso (2018)
The purpose of this study was to analyze two official documents of Christianity promulgated in the 1960s and 1970s, namely the Pastoral Constitution Gaudium et Spes in Catholicism and the Lausanne Covennant in Protestantism, with a focus on poverty in Latin America, using a bibliographical and documentary research methodology. Main theoretical references included the sociology of Max Weber in analyzing the motivations behind the documents, and the missiology of David Bosch to study the historical and theological contexts. The dissertation is structured in three chapters. In the first, we analyse the context that defines the conception of Christianity regarding the mission of the church in the nineteenth century, as well as the way in which the two Christian perspectives viewed the question of poverty. The second chapter analyzes the two documents and their social, political, and economic context of the mid-twentieth century and identifies the conception of poverty within the mission context in a new paradigm, missio Dei, which classifies poverty as an institutional and structural problem in both Christian perspectives. In the third chapter, we analyze the theoretical implications and the contradictions that the new paradigm brings to the question of the poverty of the Latin American populations, the practical repercussions with the organization of the Ecclesial Base Communities, Liberation Theology and Theology of the Integral Mission